CAUSES OF OCCURRENCE AND METHODS OF TREATMENT OF STRABISMUS - Badriddinov Oyatillo Usmonjon ugli; Kholmatova Yokutkhon Nematillaevna (Scholar Express Journals, 2022)
The article provides information on the modern classification system of strabismus causes of occurrence and methods of treatment in the practice of ophthalmology
Keywords: ophthalmology; strabismus; treatment tactics; ophthalmopathology